1989
DOI: 10.1159/000118566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensorimotor and Cognitive Performance of Acute Schizophrenic Inpatients Treated with Remoxipride or Haloperidol

Abstract: 29 acute schizophrenic patients according to DSM III and ICD-9 underwent examination of performance regarding cognitive and sensorimotor tasks at the beginning and the end of a 28-day neuroleptic treatment with remoxipride or haloperidol in a double-blind design. Psychopathological symptoms were assessed by Brief Psychiatric Rating Scale and Clinical Global Impression, extrapyramidal side effects (ESE) were rated by Simpson-Angus scale. A significant treatment effect for acoustic reaction time tasks, naming of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The effect in one of these studies (Rosse et al, 1992) may be a result of practice rather than a medication effect. The effect of haloperidol found in the other study (Classen & Laux, 1989) was not replicated in another study that also used haloperidol (Serafetinides et al, 1972). A number of factors (e.g., methodology, type of patients) could explain the discrepancy in the results.…”
Section: Nonschizophrenia Studiesmentioning
confidence: 75%
See 2 more Smart Citations
“…The effect in one of these studies (Rosse et al, 1992) may be a result of practice rather than a medication effect. The effect of haloperidol found in the other study (Classen & Laux, 1989) was not replicated in another study that also used haloperidol (Serafetinides et al, 1972). A number of factors (e.g., methodology, type of patients) could explain the discrepancy in the results.…”
Section: Nonschizophrenia Studiesmentioning
confidence: 75%
“…Their findings are limited as they defined Stroop interference as the difference between reading color words in black and naming neutral stimuli, which is not an appropriate measure of Stroop interference. Classen and Laux (1989) employed the card version of the Stroop task to compare the effects of haloperidol (a traditional dopamine blocker) and remoxipride (a dopamine receptor blocker having a selective affinity to D2-receptors) on attention. They treated 29 schizophrenia patients for 28 days and found that haloperidol reduced interference, but remoxipride had no effect on Stroop interference.…”
Section: Schizophrenia Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies reported no negative effect on SCWT of antipsychotic (Serafetinides et al 1972;Hartley & Couper-Smartt, 1978;Killian et al 1984;Berger et al 1989;Classen & Laux 1989) or antidepressive drugs (Killian et al 1984;Jones et al 1986). Likewise, no significant effect of BZD on the interference score were reported by several relevant studies (Nakano et al 1978;Griffiths et al 1986;Boulenger et al 1989).…”
Section: Discussionmentioning
confidence: 99%